1992
DOI: 10.1111/j.1365-2265.1992.tb00955.x
|View full text |Cite
|
Sign up to set email alerts
|

Results of long‐term continuous subcutaneous octreotide administration in 14 patients with medullary thyroid carcinoma

Abstract: Biological or morphological parameters of medullary thyroid carcinoma are not significantly improved in a large series of patients treated by octreotide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(24 citation statements)
references
References 8 publications
0
23
0
1
Order By: Relevance
“…The data regarding the effect of SSAs in the treatment of symptomatic MTC are controversial: in one study, this treatment significantly improved symptoms such as diarrhoea, weight loss or malaise in all of the three patients with metastatic MTC, with a parallel decrease in the calcitonin and CEA levels (Mahler et al 1990). In another study, 14 post-thyroidectomy metastatic MTC patients were treated with continuous s.c. infusion of 500 mg/day octreotide, for 90 days (Modigliani et al 1992): continuous infusion of octreotide did not induce any morphological improvement or a significant decrease in calcitonin levels; in four patients, calcitonin levels fell during treatment (between 15% and 50%), while in nine patients, calcitonin increased (from 22% to 130%) after cessation of therapy. In patients with advanced metastatic disease, the administration of octreotide combined with interferon was studied: in a study of eight patients with advanced MTC, patients received octreotide (at a starting dose of 150 mg/day s.c. for 6 months, followed by a dose of 300 mg/day s.c. for another 6 months) combined with recombinant interferon-a-2b (rIFN-a-2b) (at a dose of 5 million IU/day i.m.…”
Section: S Grozinsky-glasberg Et Al: Somatostatin Action In Netsmentioning
confidence: 84%
“…The data regarding the effect of SSAs in the treatment of symptomatic MTC are controversial: in one study, this treatment significantly improved symptoms such as diarrhoea, weight loss or malaise in all of the three patients with metastatic MTC, with a parallel decrease in the calcitonin and CEA levels (Mahler et al 1990). In another study, 14 post-thyroidectomy metastatic MTC patients were treated with continuous s.c. infusion of 500 mg/day octreotide, for 90 days (Modigliani et al 1992): continuous infusion of octreotide did not induce any morphological improvement or a significant decrease in calcitonin levels; in four patients, calcitonin levels fell during treatment (between 15% and 50%), while in nine patients, calcitonin increased (from 22% to 130%) after cessation of therapy. In patients with advanced metastatic disease, the administration of octreotide combined with interferon was studied: in a study of eight patients with advanced MTC, patients received octreotide (at a starting dose of 150 mg/day s.c. for 6 months, followed by a dose of 300 mg/day s.c. for another 6 months) combined with recombinant interferon-a-2b (rIFN-a-2b) (at a dose of 5 million IU/day i.m.…”
Section: S Grozinsky-glasberg Et Al: Somatostatin Action In Netsmentioning
confidence: 84%
“…36,55 Limited success has also been found with radio-iodinated metaiodobenzyl guanidine (MIBG) and somatostatin analogs. 56,57 Octreotide therapy can be considered for patients with metastatic disease or refractory diarrhea. 56,58 Trials using 131 I-labeled anti-CEA monoclonal antibodies have shown good tumor uptake and limited antitumor effect in up to 50% of patients for up to 26 months without significant toxicity.…”
Section: Treatment and Follow-upmentioning
confidence: 99%
“…56,57 Octreotide therapy can be considered for patients with metastatic disease or refractory diarrhea. 56,58 Trials using 131 I-labeled anti-CEA monoclonal antibodies have shown good tumor uptake and limited antitumor effect in up to 50% of patients for up to 26 months without significant toxicity. 59 External beam radiation therapy is generally considered for palliation in metastatic disease.…”
Section: Treatment and Follow-upmentioning
confidence: 99%
“…In MTC patients, various combinations of doxorubicin, 5-fluorouracil, dacarbazine, streptozocin, cyclophosphamide, and vincristine have produced response rates around 20% with symptomatic improvement in some; all responses were partial and transient, and no benefit on survival was demonstrated (4 -11). Diarrhea is incompletely controlled by loperamide, and somatostatin analogs and interferon are poorly effective to control symptoms (11,12).…”
Section: Edullary Thyroid Carcinoma (Mtc) Arisesmentioning
confidence: 99%